2018
DOI: 10.1002/cssc.201702007
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent Aqueous Solutions as Efficient Media for the Solubilization of Hardwood Xylans

Abstract: This work contributes to the development of integrated lignocellulosic-based biorefineries by the pioneering exploitation of hardwood xylans by solubilization and extraction in deep eutectic solvents (DES). DES formed by choline chloride and urea or acetic acid were initially evaluated as solvents for commercial xylan as a model compound. The effects of temperature, molar ratio, and concentration of the DES aqueous solutions were evaluated and optimized by using a response surface methodology. The results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…Somehow, ChCl:UREA allowed better dispersion of xylose crystals than other ESs surpassing the solute-solute interactions at high xylose mass fractions. The high performance of ChCl:UREA for xylose dissolution in this study is in agreement with the results reported by Morais et al [38] reporting the highest xylan solubility in this ES.…”
Section: Xylose Dissolutionsupporting
confidence: 93%
See 2 more Smart Citations
“…Somehow, ChCl:UREA allowed better dispersion of xylose crystals than other ESs surpassing the solute-solute interactions at high xylose mass fractions. The high performance of ChCl:UREA for xylose dissolution in this study is in agreement with the results reported by Morais et al [38] reporting the highest xylan solubility in this ES.…”
Section: Xylose Dissolutionsupporting
confidence: 93%
“…Although several studies have reported success using ESs in the fractionation of several biomass matrices, such as corn residues [27], corn straw [28], rice straw [29], woodchip [30], corn cob [31], and algae [32], there is still limited knowledge about their ability to dissolve each macromolecular component. There are some studies that focused on evaluating the dissolution ability of ESs for individual biomass components [24,29,[33][34][35][36] and understanding the key factors governing the dissolution process [33,[37][38][39]. For instance, Morais et al [38] demonstrated that xylans can be solubilized in aqueous solutions of ESs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique can be effectively used for the determination of the particle size and their dissolution rate kinetics, hence being studied in this work. Chitin dissolution in two alkaline DESs has already been shown by others, yet it is possible to prepare eutectic mixtures with different characteristics, for instance, pH . In this sense, herein four distinct DESs were selected to further extend this study as different hydrogen bonds can be established between chitin and these solvents.…”
Section: Resultsmentioning
confidence: 92%
“…These dissolution results showed that it is possible to dissolve chitin in DESs with different pH and not only in alkaline ones . Therefore, an acidic ([Ch]Cl:LA), a neutral (Bet:G) and an alkaline ([Ch]Cl:U) DESs were selected to perform the homogenous N‐deacetylation of chitin using a final 30 wt% concentration of NaOH.…”
Section: Resultsmentioning
confidence: 99%